Efficiency of IPS and its effect on Bangladesh Power systems - Sarwar, Rashed (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.